Lipids of lung and lung fat emboli of the toothed whales (Odontoceti) - Arregui Gil, Marina; Glandon, Hillary Lane; Bernaldo De Quirós Miranda, Yara; Felipe Jiménez, Idaira Del Carmen; Consoli, Francesco; Caballero Cansino, María José; Koopman, Heather N.; Fernández Rodríguez, Antonio Jesús (Scientific Reports, 2020)
Lipids are biomolecules present in all living organisms that, apart from their physiological functions, can be involved in different pathologies. One of these pathologies is fat embolism, which has been described histologically in the lung of cetaceans in association with ship strikes and with gas and fat embolic syndrome. To assess pathological lung lipid composition, previous knowledge of healthy lung tissue lipid composition is essential; however, these studies are extremely scarce in cetaceans. In the present study we aimed first, to characterize the lipids ordinarily present in the lung tissue of seven cetacean species; and second, to better understand the etiopathogenesis of fat embolism by comparing the lipid composition of lungs positive for fat emboli, and those negative for emboli in Physeter macrocephalus and Ziphius cavirostris (two species in which fat emboli have been described). Results showed that lipid content and lipid classes did not differ among species or diving profiles. In contrast, fatty acid composition was significantly different between species, with C16:0 and C18:1ω9 explaining most of the differences. This baseline knowledge of healthy lung tissue lipid composition will be extremely useful in future studies assessing lung pathologies involving lipids. Concerning fat embolism, non-significant differences could be established between lipid content, lipid classes, and fatty acid composition. However, an unidentified peak was only found in the chromatogram for the two struck whales and merits further investigation. 1,24 4,379 Q1 Q1 SCIE